Pengembangan silabus penguatan pendidikan karakter berbasis profil pelajar pancasila - Numertayasa, I Wayan; Kusuma, I Komang Nada; Astuti, Ni Putu Eni (Universitas Ahmad Dahlan, 2022)
This study aims to (1) determine the needs of teachers in an effort to carry out character education strengthening activities, (2) develop a prototype of character education strengthening syllabus development based on Pancasila student profiles and (3) design components of syllabus development based on character education strengthening programs. from the Ministry of Education and Culture. This research method uses research and development design. The location of this research is at SDN 6 Pempatan which is located in Banjar Pempatan, Pempatan Village, Rendang District, Karangasem Regency, Bali Province. This research uses closed questionnaire and interview data collection techniques. This study uses two data analysis techniques, namely descriptive qualitative and descriptive statistical analysis techniques. Qualitative descriptive analysis technique was used to process the interview data. Descriptive statistical analysis technique was used to process closed questionnaire data and the effectiveness of the syllabus through a questionnaire instrument. The level of validity of the syllabus was analyzed by descriptive statistics using a Likert scale. The results of this study are (1) teachers need a reference in the form of a syllabus to make it easier to carry out character education activities (2) The product validity results show a score of 76 so that it is in the definitely valid category. These results prove that the prototype of the syllabus product for strengthening character education based on the Pancasila student profile is definitely feasible to use.